WSe2/rGO hybrid structure: A stable and efficient catalyst for hydrogen evolution reaction. (1st February 2018) - Li, Jing; Liu, Ping; Qu, Yan; Liao, Tingdi; Xiang, Bin
Abstract: The number of exposed active sites in a catalyst plays a key role in determining its catalytic performance. However, the aggregation effect in nanostructured catalysts causes much less reactive sites exposed. In this paper, we report a novel structure of WSe2 /rGO with highly exposed WSe2 active edge sites by uniformly imbedding the rGO between each WSe2 nanosheets. With the introduction of rGO, the electron transport property of the WSe2 /rGO hybrid structure has also been enhanced. The structure and composition of the samples were investigated by the X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy. Our electrochemical characterizations confirm that the WSe2 /rGO hybrid structure exhibits enhanced electrochemical catalytic performance with a Tafel slop of 85 mV/dec for HER, much smaller than that of the pure WSe2 . Graphical abstract: SEM image of the WSe2 /rGO hybrid structure and the Tafel plots of WSe2 /rGO and WSe2 as well as commercial Pt. Highlights: We report a novel 1D WSe2 nanowires with homogeneous distribution of rGO. The rGO enhances the conductivity and suppresses the aggregations of the WSe2 . The composites exhibit impressive performances in the HER.